Treatment of anger problems in previously deployed post‐911 veterans: A randomized controlled trial. Issue 4 (8th December 2021) - Shea, M. Tracie; Stout, Robert L.; Reddy, Madhavi K.; Sevin, Elizabeth; Presseau, Candice; Lambert, Jennifer; Cameron, Amy
Abstract: Background: Problems with anger and aggression affect many veterans who have deployed to a warzone, resulting in serious impairment in multiple aspects of functioning. Controlled studies are needed to improve treatment options for these veterans. This randomized controlled trial compared an individually delivered cognitive behavioral therapy adapted from Novaco's Anger Control Therapy to a manualized supportive therapy to control for common therapeutic factors. Methods: Ninety‐two post‐911 veterans deployed during Operation Enduring Freedom (OEF), Operation Iraqi Freedom (OIF), or Operation New Dawn (OND) with moderate to severe anger problems were randomized to receive the cognitive behavioral intervention (CBI) or the supportive intervention (SI). Anger, aggression, multiple areas of functioning and quality of life were assessed at multiple time points inclu3‐ and 6‐month follow‐up. Results: Hierarchical linear modeling (HLM) analyses showed significant treatment effects favoring CBI for anger severity, social and interpersonal functioning, and quality of life. The presence of a PTSD diagnosis did not affect outcomes. Conclusions: CBI is an effective treatment for OEF/OIF/OND veterans with anger problems following deployment, regardless of PTSD diagnosis.